2015
DOI: 10.1371/journal.pone.0120539
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Quality Evaluation of Low Tube Voltage Coronary CT Angiography Using Low Concentration Contrast Medium

Abstract: PurposeTo compare the image quality of prospectively ECG-gated low voltage coronary computed tomography angiography (CTA) with an administration of low concentration contrast medium.Method and MaterialsA total of 101 patients, each with a heart rate below 65 beats per minute (BPM), underwent a prospectively ECG-gated axial scan in CT coronary angiography on a 64-slice CT scanner. All patients were allocated in three groups (group A: n=31, 80kVp, 300 mgI/ml; group B: n=34, 100kVp, 300 mgI/ml; group C: n=36, 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…e injection protocols were defined with help of a formula, which has been explained extensively elsewhere [20] and can be found in Appendix 1. Besides personalization to these patient characteristics, the injection protocol was adapted to the tube voltage, as described in previous studies [21][22][23][24][25]. e following formulas were used: With BW in kg and L � length in cm (iii) CO: flow rate � 0.008916 * kV * CO (b) CO according to an adapted Katori formula [27] CO � (4.874 − 0.023 * age) * BSA With age in years and BSA � body surface area e formulas shown above determined the flow rates for both test bolus and main bolus.…”
Section: Ethics and Study Designmentioning
confidence: 99%
“…e injection protocols were defined with help of a formula, which has been explained extensively elsewhere [20] and can be found in Appendix 1. Besides personalization to these patient characteristics, the injection protocol was adapted to the tube voltage, as described in previous studies [21][22][23][24][25]. e following formulas were used: With BW in kg and L � length in cm (iii) CO: flow rate � 0.008916 * kV * CO (b) CO according to an adapted Katori formula [27] CO � (4.874 − 0.023 * age) * BSA With age in years and BSA � body surface area e formulas shown above determined the flow rates for both test bolus and main bolus.…”
Section: Ethics and Study Designmentioning
confidence: 99%
“…Therefore, only 20 studies were finally selected for analysis. [15][16][17][18][19][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] A detailed overview of the inclusion and data extraction processes is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Whereas for triphasic injection, three distinct boluses were used; an initial undiluted contrast bolus followed by a CM and saline mixture, and then completed by a saline flush. Compared to 120 kVp, CM reduction was applied in seven studies at 80 kVp [17][18][19]31,33,38,41 and eight studies at 100 kVp. 27,[34][35][36][37][38][39]41 However, only two studies at 80 kVp, 18,19 and five studies at 100 kVp 34,35,37,39,41 reported similar vessel contrast enhancement compared to those at 120 kVp.…”
Section: Radiation Dose and Image Qualitymentioning
confidence: 99%
“…For example, the International Telecommunication Union (ITU) has formulated lots of international standards to implement the subjective image quality assessment for some purposes [5][6][7]. And according to different application fields, the SIEA can be used in the medical imaging terminal research [8], the mobile device design [9], the computer science study [10], and the communication equipment development [11], etc. In terms of different research targets, it also can be used for the medical image [12], the facsimile image [13], the compressed image [14], the segmented image [15], the stereoscopic image [16], the omnidirectional image [17], and the remote image [18], etc.…”
Section: Introductionmentioning
confidence: 99%